2017
DOI: 10.1097/bot.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Corrective Osteotomy of Malunited Pediatric Radial Neck Fractures—Three-Dimensional Postoperative Accuracy and Clinical Outcome

Abstract: Neglected or incorrect treatment of pediatric radial neck fractures may lead to symptomatic malunions. Computer-assisted corrective osteotomies with patient-specific guides have been proposed as a promising technique for the reconstruction of malunited long bone deformities. The aim of this study was to evaluate the accuracy and clinical outcome of this technique in children with malunited fractures of the radial neck. Four children [2 boys, 2 girls; mean age 12 (10-16) years] underwent computer-assisted closi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…But as an incision surgery, it cannot avoid the negative impact on children [ 5 , 9 ]. With the development of minimally invasive technology, minimally invasive treatment methods like closed reduction, Kirschner wires and Métaizeau technique are gradually widely applied to clinically treat children with radial neck fractures [ 8 10 ]. For elderly children radius neck fracture, ordinary X-ray and C-arm light machine can clearly show the fracture situation, easy diagnosis, and intraoperative operation that are more purposeful.…”
Section: Introductionmentioning
confidence: 99%
“…But as an incision surgery, it cannot avoid the negative impact on children [ 5 , 9 ]. With the development of minimally invasive technology, minimally invasive treatment methods like closed reduction, Kirschner wires and Métaizeau technique are gradually widely applied to clinically treat children with radial neck fractures [ 8 10 ]. For elderly children radius neck fracture, ordinary X-ray and C-arm light machine can clearly show the fracture situation, easy diagnosis, and intraoperative operation that are more purposeful.…”
Section: Introductionmentioning
confidence: 99%
“…RNFs are similar to femoral neck fractures, where the blood supply is destroyed, and the radial head is prone to necrosis. Several recent studies have suggested closing manipulation or Kirschner’s wire reduction to treat pediatric RNF and reduce complications 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have described the use of the guide as a promising technique. They have demonstrated good clinical outcomes [ 19 25 ] and high accuracy [ 26 28 ] in performing corrective osteotomies for upper limb deformities, and have reported its utility for the intra-articular correction of the distal radius [ 29 , 30 ]. The 1.0-mm expansion of the physeal bar was defined as a target knowing that approximately 0.5 mm is the mean error in creating the models [ 14 ], and the diameter of the K-wires mentioned later is 0.5 mm.…”
Section: Discussionmentioning
confidence: 99%